Keeping the Ledger Balanced during Pregnancy. Issue 2 (3rd April 2022) - Eddy, Brandon P.; Springer, Paul; Sibley, D. Scott; Turns, Brie; Fife, Stephen T.
ABSTRACT: Couples experiencing pregnancy and the transition to parenthood face many challenges. One of the most difficult challenges is attempting to remain balanced in their relationship. In order to discover how couples maintain balance, researchers conducted a secondary analysis of qualitative data using a contextual family therapy lens to investigate how couples keep their relationship ledger balanced during pregnancy. Results indicate that four key components help couples maintain balance in the relationship, namely: 1) Give and take, 2) Relational ethics, 3) Destructive and Constructive Entitlement, and 4) Exoneration. Couples who give attention to these four aspects were more balanced in their relationship and reported navigating the transition to parenthood and pregnancy more effectively. Results from this study provide a framework for therapists to guide couples in discussing important topics that should be discussed throughout the transition to parenthood.